2009
DOI: 10.1111/j.1365-2141.2009.07954.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory correlates for a phase II trial of romidepsin in cutaneous and peripheral T‐cell lymphoma

Abstract: Summary Romidepsin has shown promise in the treatment of T‐cell lymphomas, and so we evaluated molecular endpoints gathered from 61 patients enrolled on a phase II trial of romidepsin in cutaneous and peripheral T‐cell lymphoma at the National Institutes of Health. The endpoints included histone H3 acetylation and ABCB1 gene expression in peripheral blood mononuclear cells (PBMCs); ABCB1 gene expression in tumour biopsy samples; and blood fetal haemoglobin levels (HbF), all of which were increased following ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 45 publications
2
63
0
Order By: Relevance
“…Quantitative PCR analysis for a selection of MAPK downregulated genes was confirmed in another subset of patients and contrasted with ABCB1 ( Figure 5B), which we previously found upregulated in peripheral blood samples taken from patients treated with romidepsin. 14 These results demonstrate that romidepsin alters expression of genes controlled by the MAPK pathway, a finding consistent with a role for perturbation of this pathway in romidepsin effect.…”
Section: Short-term Romidepsin Treatment Combined With Mek Inhibitionsupporting
confidence: 69%
See 2 more Smart Citations
“…Quantitative PCR analysis for a selection of MAPK downregulated genes was confirmed in another subset of patients and contrasted with ABCB1 ( Figure 5B), which we previously found upregulated in peripheral blood samples taken from patients treated with romidepsin. 14 These results demonstrate that romidepsin alters expression of genes controlled by the MAPK pathway, a finding consistent with a role for perturbation of this pathway in romidepsin effect.…”
Section: Short-term Romidepsin Treatment Combined With Mek Inhibitionsupporting
confidence: 69%
“…30 Although Pgp confers transporter-mediated resistance to romidepsin, this was not observed in the clinical samples studied. 14 We thus focused on nonPgp resistance mechanisms, evaluating HuT78 CTCL sublines independently selected in romidepsin in the presence of verapamil or valspodar to prevent the emergence of Pgp-mediated resistance. 17 We probed potential resistance mechanisms in the romidepsin-resistant lines by using a high-throughput TaqMan-based quantitative RT-PCR assay, 31 finding increased INSR expression as well as increased IR protein and phospho-MEK expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,28 Although the half-life is relatively short at 3 hours, exploratory pharmacodynamic studies demonstrated increased histone acetylation in PBMCs extending from 4 to 48 hours. 29 These studies, which included both patients from the CTCL cohort and 18 of the 47 patients with PTCL reported here, *Two patients were excluded from response assessment: one patient discovered to be ineligible for enrollment after receiving the first dose and one patient whose T-cell lymphoma was reclassified as DLBCL. BLOOD, 2 JUNE 2011 ⅐ VOLUME 117, NUMBER 22 For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…24 Romidepsin is also likely to be a substrate of the organic transporter, OATP1B3, an influx transporter encoded by SLCO1B3, because other cyclic peptides have been shown to interact with the same transporter. 25,26 However, the role of single nucleotide polymorphisms in CYP3A4/5, ABCB1, and SLCO1B3 in the individual variability of romidepsin disposition has not been quantitatively assessed. Population pharmacokinetic analysis was performed in 98 patients enrolled in a Phase II multicenter clinical trial of romidepsin in patients with CTCL and PTCL and dosed at 14 mg/m 2 or 18 mg/ m 2 on day 1 during their first treatment cycle.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%